Changes in Infant Mortality in a Ukrainian County Town between 1807 and 1910 (Based on the Metric Records of Romny, Poltava Governorate) (City: History, Culture, Society, 2023)
The article deals with infant and child mortality and its changes during the 19th century in a Ukrainian county town, based on the example of the population of the county town Romny. The main sources for this research are metrical books of the Church of Ascension in Romny. For the research purposes, we used the data from two chronological periods, namely 20 years at the beginning of the century (1807–1826) and 17 years at the end of the 19th — beginning of the 20th centuries (1891–1910, except the years absent in the sources that is 1893, 1894 and 1899). First, the article considers the main components of the demographic behaviour of the population: birth rate, mortality rate, and the rate of natural population growth. It also contains calculations of infant mortality and under-five mortality rates. Secondly, the article examines the distinctive aspects of child mortality structure in the context of indicators characteristic for the population across all age groups. It also analyzes the structure of child mortality in one-year age groups in more detail. The obtained data allow us to make assumptions about changes in the causes of infant and child death that have occurred over the course of a hundred years, as well as changes in seasonal fluctuations of infant and child mortality. The article concludes that, despite the progress of medicine throughout the 19th century, infant mortality still remained very high. However, we see significant changes in the context of child mortality over the age of several years, which almost doubled the probability of survival to 5 years. This, in turn, means that the most significant changes in life expectancy, mortality, etc., for those times are associated with the fight against children’s epidemic diseases (primarily smallpox).
Keywords: mortality; population reproduction; metrical books; county town; Romny; 19th century; life quality; history of childhood